Update on Amniocentesis - Hanprasertpong, Jitti; Hanprasertpong, Tharangrut (Thai Journal of Obstetrics and Gynaecology, 2024)
Amniocentesis is a common prenatal diagnostic procedure. All steps before, during and after the procedure are essential and should be carefully performed. Moreover, there are several interesting and update aspects. This article aims for updating of amniocentesis in pregnant women with specific conditions, such as those infected with human immunodeficiency virus (HIV), those taking antiplatelet medications (such as aspirin), those who are obese, those who are infected with hepatitis B, and those experiencing a twin pregnancy.